1988
DOI: 10.4049/jimmunol.141.9.2959
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endogenous and synthetic sex steroids on the clearance of antibody-coated cells.

Abstract: Steroid hormones may influence the clinical expression of immunologic disease; however, their mechanism of action is uncertain. By using an experimental model, we studied the effect of sex steroids on the clearance of antibody-coated cells by macrophages in the spleen and liver. Progesterone significantly inhibited the clearance of IgG-coated E by splenic macrophages, whereas no effect was observed on the clearance of heat-altered E. This effect of progesterone was observed at serum concentrations which are at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…88 The effect of danazol may also be partially explained by it being a sex steroid analogue like progesterone, which can downregulate the expression of Fc receptors in monocytes, thereby decreasing immune-mediated clearance of platelets. 89,90 Recent studies revealed associations of clonal T-cell populations with CTP. Füreder and Fogarty reported the first two cases with clonal T-cell receptor (TCR) rearrangement.…”
Section: Thrombocytopenia-based Ctpmentioning
confidence: 99%
See 1 more Smart Citation
“…88 The effect of danazol may also be partially explained by it being a sex steroid analogue like progesterone, which can downregulate the expression of Fc receptors in monocytes, thereby decreasing immune-mediated clearance of platelets. 89,90 Recent studies revealed associations of clonal T-cell populations with CTP. Füreder and Fogarty reported the first two cases with clonal T-cell receptor (TCR) rearrangement.…”
Section: Thrombocytopenia-based Ctpmentioning
confidence: 99%
“…started a patient on danazol, potentially due to its ability to reduce oestrogen production, which resulted in a prolonged platelet response 88 . The effect of danazol may also be partially explained by it being a sex steroid analogue like progesterone, which can downregulate the expression of Fc receptors in monocytes, thereby decreasing immune‐mediated clearance of platelets 89,90 …”
Section: Underlying Pathogenic Elements Associated With Susceptibilit...mentioning
confidence: 99%